Modelling ultrafine particle number concentrations at address resolution in Denmark from 1979 to 2018 - Part 2: Local and street scale modelling and evaluation. (1st November 2021) - Ketzel, Matthias; Frohn, Lise M.; Christensen, Jesper H.; Brandt, Jørgen; Massling, Andreas; Andersen, Christopher; Im, Ulas; Jensen, Steen Solvang; Khan, Jibran; Nielsen, Ole-Kenneth; Plejdrup, Marlene S.; Manders, Astrid; et al.
Abstract: Modelling of ambient particle number concentrations (PNC) has been implemented in the Danish air quality modelling system DEHM/UBM/AirGIS and evaluated with long-term measurements. We implemented particle dynamical processes in the regional scale model DEHM using the M7 aerosol dynamics module (presented in the accompanying article by Frohn et al., 2021), and we developed models for PNC at the local scale (UBM) and street scale (OSPM), in a first approximation without including the particle dynamics as presented in this article. Outdoor concentration estimates are provided at the front door of all residential address locations in Denmark for the past 40 years (1979–2018) with a spatial resolution of 1 km × 1 km taking all emission sectors in Denmark into account and additionally at the street location, with significant traffic (>500 vehicles/day). We evaluated our model with up to 18-year long measurement time series of particle number size distributions (PNSD) at Danish street, urban and rural background stations. Two particle size ranges were used for evaluation: PNC>10 (count of particles with diameter larger than 10 nm) and PNC30_250 (diameter range 30–250 nm), in order to exclude nucleation events from the measurements and to obtain a consistent long-term measured time series. When comparing our model estimates with PNC30_250 measurements, we obtain Pearson correlation coefficients (Rp ) in the range 0.39–0.95 depending on station location (street, urban background, rural) and averaging time (hour, day, month, year). The highest correlations were found for yearly averages at a monitoring station located at a street with dense traffic (Rp  = 0.95) whereas shorter time averages and comparisons with monitoring stations at urban and rural background locations provided lower correlations. The model performance for PNC in terms of correlation coefficients with respect to measurements is comparable to the performance for other pollutants such as NOX, PM2.5 and better than the performance for PM10 . The model generally overestimated the observed concentrations, Normalized Mean Bias (NMB) was in the range 6%–190% compared to PNC>10 and 90%–290% compared to PNC30_250 . These relatively high NMBs are probably caused by uncertainties in the modelling process, especially the estimation of particle number emissions, which largely determine the ambient concentrations of PNC. Furthermore, uncertainties might as well originate from the complexity of modelling particle dynamical processes accurately and the great challenges in performing long-term PNC measurements. The presented model can estimate PNC at all Danish addresses over the last 40 years with a 1-h time resolution. The data seem to provide a good indication of the relative differences in PNC at Danish addresses. Highlights: Particle number concentrations (PNC) implemented in the Danish air quality modelling system DEHM/UBM/AirGIS. Outdoor concentrations are provided at the front door of all residential addresses in Denmark for 40 years (1979–2018) Spatial resolution of 1 km × 1 km taking all emission sectors in Denmark into account. Additionally at the street locations consider the local traffic contribution, all done in 1 hour time resolution. Comparing model with PNC30_250 measurementsgives Pearson correlation coefficients in the range 0.39–0.95. Model overestimated the observed concentrations, Normalized Mean Bias in the range 6%–190% compared to PNC>10 .